2020
DOI: 10.1088/1757-899x/870/1/012065
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Canadian Water Quality Index in Alhindya Barrage, Euphrates River

Abstract: Recently, water quantity is decreasing due to high temperatures in summer and reducing the water quotas of Euphrates River in Iraq from the neighboring countries. These factors may increase turbidity and concentration of elements in Euphrates River especially near Alhindya Barrage, Babylon Governorate, Iraq. Thus, Euphrates River may not be valid for drinking and irrigation purposes in upstream of Alhindya Barrage. The aim of this study was to investigate the water quality upstream of Alhindya Barrage, Euphrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The frequencies (F2) is the No.of times these-objectives arenot-met as well as amplitude named as F3 the-amounts via That theobjectives werenot mett. The WQI produces as the number between 0 as polluted water while 100 as excellent Hommadi, A H et al,2020 water quality as shown in Table.6.…”
Section: Table (5)mentioning
confidence: 99%
“…The frequencies (F2) is the No.of times these-objectives arenot-met as well as amplitude named as F3 the-amounts via That theobjectives werenot mett. The WQI produces as the number between 0 as polluted water while 100 as excellent Hommadi, A H et al,2020 water quality as shown in Table.6.…”
Section: Table (5)mentioning
confidence: 99%